2023
DOI: 10.3390/geriatrics8050091
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Diminished Human Relationships Are Associated with Poor Sleep Quality in Japanese Older Adults: A Cross-Sectional Study

Hitomi Matsuda,
Thomas Mayers,
Naoki Maki
et al.

Abstract: The purpose of this study was to examine the association between sleep quality, frailty, and human relationships in Japanese older adults (aged 65 years and above, excluding those certified as requiring long-term care). This cross-sectional study used a questionnaire survey to gather demographic information, data on frequency of conversation and conversation partners, and employed the following validated instruments: Kihon Checklist (KCL), a Japanese instrument used to determine the care needs and frailty of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In this study, the presence of dysphagia risk in older individuals led to poor sleep quality. Poor sleep quality in older individuals is not only associated with cognitive impairment [ 38 ] but also with deterioration in self-rated health status [ 39 ], decreased physical capabilities [ 40 ], and frailty [ 12 ]. Dysphagia is also significantly correlated with skeletal muscle strength in community-dwelling older individuals [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the presence of dysphagia risk in older individuals led to poor sleep quality. Poor sleep quality in older individuals is not only associated with cognitive impairment [ 38 ] but also with deterioration in self-rated health status [ 39 ], decreased physical capabilities [ 40 ], and frailty [ 12 ]. Dysphagia is also significantly correlated with skeletal muscle strength in community-dwelling older individuals [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the effect of dysphagia on sleep quality remains largely unexplored, the potential influence of impaired swallowing function on sleep quality should be considered. Poor sleep quality has been associated with frailty [ 12 ], and poorer sleep quality and shorter sleep duration might be associated with Alzheimer's disease [ 13 ] in older populations. Furthermore, some older adults may be unaware of their poor sleep quality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a reciprocal relationship between loneliness and sleep quality is acknowledged. Studies suggest that inadequate sleep quality in China and Japan may heighten feelings of loneliness among older adults 21 , 22 . Conversely, a meta-analysis revealed that loneliness in older adults can heighten the risk of diminished sleep quality 23 .…”
Section: Introductionmentioning
confidence: 99%